Mutation of Tyr137 of the universal Escherichia coli fimbrial adhesin FimH relaxes the tyrosine gate prior to mannose binding. (2017) - Rabbani, Said; Krammer, Eva-Maria; Roos, Goedele; Zalewski, Adam; Preston, Roland; Eid, Sameh
No abstract available